The socio-technical factors in the use of GIS at the Planning Departments of the Kuala Lumpur City Hall - Mohd. Hussain, Mohd. Ramzi; Johar, Foziah (MIP, 2010)
The development of GIS has progressed dramatically in recent years and its use has proliferated in government planning departments in Malaysia. The majority of the information utilised for planning activities such as development control has a geographical component. The argument is that creating a successful GIS within planning organisation must be seen from a socio-technical rather than just a technical perspective. This paper presents an investigation on the use of GIS technology, specifically at the Department of Urban Planning (DUP) and the Master Plan Department (MPD) in the Kuala Lumpur City Hall (KLCH) Malaysia. The paper employed a combination of a case study, a semi-structured interview, and a survey questionnaire and observations of the activities of the department. The findings demonstrate that the skill, knowledge and training influence the planning staff to use GIS effectively. It is proved that the manner in which these factors interact with the GIS determines the processes which affect the utilisation process of automated systems. The paper concludes that a situation of mutual dependency whereby the socio-technical factors influence the utilisation of GIS and, at the same time, the technology has various impacts in terms of benefits and problems on the planning departments and staff involved. Thus, the identification of the socio-technical factors and the manner in which the users interact enables greater understanding of the processes affecting the effective use of GIS at the DUP and MPD, KLCH.